(untitled) (Research, Society and Development, 2021)
Mucoceles are benign pseudocystic lesions, whose main etiological factors are trauma and ductal obstruction, with the rupture of a duct in the salivary gland and leakage of mucin into the adjacent soft tissues. They are characterized by being asymptomatic and often present spontaneous rupture. Histologically, they are made up of a cystic wall devoid of epithelium, outlined by granulation tissue and inflammatory cells. Mucoceles usually present as dome-shaped mucous swellings, which can vary in size from 1 to 2 mm to a few centimeters, characterized as a floating lesion, although some may be firm on palpation. The evolution time reported for this lesion varies from a few days to several years, and the most common site of involvement for this phenomenon is the lower lip. Some mucoceles are self-limiting, with spontaneous rupture and scarring, however, many of these lesions are chronic in nature, and local surgical excision may be necessary. The aim of this study was report a clinical case of mucocele on the lower lip. The surgical removal of the mucocele proved to be an effective and safe technique in the case in question, enabling the histopathological diagnosis of the lesion.